Collaborative- Based Physical Education and Sports Management Learning Media Teaching Style App In Assisting the Teaching Practitioner Program-Independent Campus - Ilahi, Bogy Restu; Septian Raibowo; Andika Prabowo; Andes Permadi (UNIB Press, 2024)
This research aims to develop Learning Media for Physical Education and Sports Management Based on a Collaborative Teaching Style App to Help the Independent Campus Teaching Practitioner Program. This research uses the Research and Development (R&D) method which refers to the 4D ( four-D ) research and development model, namely defining , designing , developing and disseminating . The developed Collaborative Teaching Style App -based learning media will be tested on students taking the Physical Education and Sports Management course, FKIP UNIB Physical Education Study Program. The research instruments used to collect data in this study used questionnaires and test techniques. There are three questionnaires that will be distributed in this research, namely a material expert questionnaire, a media expert validation questionnaire, and a student response questionnaire. The aim of distributing the questionnaire was to determine the feasibility of developing the learning media that the researchers created. The technical test is in the form of an evaluation which aims to determine the extent of students' understanding of the material after the Collaborative Teaching Style App -based learning media has been tested. As a result, the total score obtained from the combined validation of material experts, media and users was 139.5 or obtained an average score of 4.1, which means that the Learning Media for Physical Education and Sports Management is Based on Collaborative Teaching Style App in Helping Teaching Practitioner Programs. The Merdeka Campus that researchers developed is included in the category suitable for use in learning activities